AUDIT PENGGAJIAN DAN RISIKO KARYAWAN FIKTIF: STRATEGI DETEKSI AUDITOR - Situmorang, Rut (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
Ghost employees are a form of payroll fraud that can lead to significant financial loss and undermine organizational integrity. This study aims to develop an effective audit detection strategy by combining traditional audit techniques with technology-based approaches to identify and prevent ghost employee practices. The research employs a literature review method using a qualitative descriptive approach, analyzing both national and international studies and references. The findings reveal that effective detection strategies include periodic payroll audits, employee data verification, the use of technologies such as biometrics and data analytics, and the proactive role of internal audit in strengthening internal controls. These results affirm that an integrated audit approach supported by information technology can enhance the effectiveness of detecting ghost employees and promote a transparent and accountable payroll system.